1994
DOI: 10.1002/hipo.450040407
|View full text |Cite
|
Sign up to set email alerts
|

Potassium‐induced long‐term potentiation in area CA1 of the hippocampus involves phospholipase activation

Abstract: Previous studies have shown that potassium-induced long-term potentiation (LTP) of the Schaffer collateral/commissural synapses in area CA1 of the hippocampus shares common properties with tetanus-induced LTP. In the present investigation, we performed electrophysiological and binding experiments on CA1 hippocampal slices to evaluate the location and nature of the changes underlying potassium-induced LTP. Paired-pulse facilitation, which represents an index of transmitter release, was markedly reduced by potas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 49 publications
3
22
0
Order By: Relevance
“…At the molecular level, the rise in intracellular calcium concentration mediated by NMDA receptor activation has been proposed to stimulate various calcium-dependent enzymatic processes that could convert the induction signal into long-lasting changes in AMPA receptor properties (Baudry and Lynch, 1993;Wang and Kelly, 1996). Interestingly, pretreatment of rat brain sections with exogenous calcium was found to enhance 3 H-AMPA binding in the hippocampus (Tocco et al, 1992b), and this ability of calcium to modulate AMPA receptors is consistent with previous data showing that LTP appearance in the hippocampal formation is associated with increased AMPA binding (Bernard et al, 1994;Maren et al, 1993;Tocco et al, 1992a).…”
Section: Introductionsupporting
confidence: 79%
“…At the molecular level, the rise in intracellular calcium concentration mediated by NMDA receptor activation has been proposed to stimulate various calcium-dependent enzymatic processes that could convert the induction signal into long-lasting changes in AMPA receptor properties (Baudry and Lynch, 1993;Wang and Kelly, 1996). Interestingly, pretreatment of rat brain sections with exogenous calcium was found to enhance 3 H-AMPA binding in the hippocampus (Tocco et al, 1992b), and this ability of calcium to modulate AMPA receptors is consistent with previous data showing that LTP appearance in the hippocampal formation is associated with increased AMPA binding (Bernard et al, 1994;Maren et al, 1993;Tocco et al, 1992a).…”
Section: Introductionsupporting
confidence: 79%
“…This finding is in line with previous data showing low levels of mRNA of cPLA 2 (Molloy et al 1998;Kishimoto et al 1999) and a dominant iPLA 2 activity over cPLA 2 activity in rat hippocampus (Yang et al 1999). Despite the low levels of mRNA and low activity of cPLA 2 , there are some evidences for an involvement of cPLA 2 in LTP induction in rat hippocampus (Bernard et al 1994;Weichel et al 1999). There is one instance in which it appears to be possible to ascertain whether the inhibitory effects of MAFP and PACOCF 3 are due to cPLA 2 or iPLA 2 , through the parallel use of BEL.…”
Section: Discussionmentioning
confidence: 97%
“…Hence, PLA 2 inhibition in rat hippocampal slices prevented LTP induction in the CA1 region mediated by an NMDA-sensitive mechanism and decreased [ 3 H]AMPA binding observed after LTP induction (Bernard et al 1994). In vivo LTP induction in rat hippocampus activated PLA 2 , which consequently reduced phosphatidylcholine and increased free AA levels (Clements et al 1991).…”
Section: Introductionmentioning
confidence: 97%
“…AA levels, the main products of cPLA2, have been implicated in various roles relevant to AD such as inflammatory response, synaptic transmission, and oxidative stress. Several studies have shown that there is likely a feedback loop between AA production and synaptic strength, long-term potentiation, as well as NMDAR and AMPAR levels in dendritic spines [34,77,78]. How AA inhibition mediates neuroprotection has not been completely elucidated, however.…”
Section: Phospholipase A2mentioning
confidence: 99%